Astragalus polysaccharide attenuates metabolic memory-triggered ER stress and apoptosis via regulation of miR-204/SIRT1 axis in retinal pigment epithelial cells. Issue 1 (21st January 2020) - Peng, Qing-Hua; Tong, Ping; Gu, Li-Min; Li, Wen-Jie
Abstract: Background: ' Metabolic memory' of early hyperglycaemic environment has been frequently suggested in the progression of diabetic retinopathy (DR). Retinal pigment epithelial (RPE) cells are crucial targets for DR initiation following hyperglycaemia. Astragalus polysaccharides (APS) has been long used as a traditional Chinese medicine in treating diabetes. In the present study, the preventive effects and mechanisms of APS on metabolic memory-induced RPE cell death were investigated. Methods: The expressions of miR-204 and SIRT1 were determined by reverse transcription quantitative PCR (RT-qPCR). Dual luciferase assay was applied to detect the potential targeting effects of miR-204 on SIRT1. SIRT1, ER stress and apoptosis related proteins were monitored using Western blotting. Apoptosis was assessed by TUNEL assay and Annexin V/PI staining followed by flow cytometry analysis. MiR-204 mimics and shSIRT1 were applied for miR-204 overexpression and SIRT1 knockdown, respectively. Results: High glucose exposure induced metabolic memory, which was accompanied with sustained dysregulation of miR-204/SIRT1 axis, high level of ER stress and activation of apoptotic pathway even after replacement with normal glucose. Pre-treatment with APS concentration-dependently reversed miR-204 expression, leading to disinhibition of SIRT1 and alleviation of ER stress-induced apoptosis indicated by decreased levels of p-PERK, p-IRE-1, cleaved-ATF6, Bax, cleaved caspase-12, -9, -3, and increased levels of Bcl-2 and unleaved PARP. The effects of APS on RPE cells were reversed by either miR-204 overexpression or SIRT1 knockdown. Conclusions: We concluded that APS inhibited ER stress and subsequent apoptosis via regulating miR-204/SIRT1 axis in metabolic memory model of RPE cells.